2022
DOI: 10.1590/fst.10322
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of oat milk with probiotic Lacticaseibacillus casei AP improves the quality of kefir produced from goat milk

Abstract: In this study, we evaluated the quality of kefir with combined additions of oat milk (8, 12, and 16% w/v) and Lacticaseibacillus casei AP (2 and 4% v/v), and observed the products' physicochemical characteristics (nutrient content, pH and acidity, viscosity and syneresis, ethanol concentration, and fatty acid profiles), microbiological characteristics (total lactic acid bacteria, total plate count, total probiotic, and total yeast), and sensory characteristics. The result showed that an increasing level of oa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The highest assessment was in the 30-day storage treatment which had a characteristic sour aroma and no musty or goat smell. While in the study of Wulansari et al (2022), the combination of adding wheat milk (8,12, and 16%) and the addition of L. casei AP (2% and 4%) did not affect the aroma of goat's milk kefir.…”
Section: Kefirmentioning
confidence: 69%
See 2 more Smart Citations
“…The highest assessment was in the 30-day storage treatment which had a characteristic sour aroma and no musty or goat smell. While in the study of Wulansari et al (2022), the combination of adding wheat milk (8,12, and 16%) and the addition of L. casei AP (2% and 4%) did not affect the aroma of goat's milk kefir.…”
Section: Kefirmentioning
confidence: 69%
“…The research of Setyawardani et al (2017) observed that the storage of kefir for 20 days is the most preferred treatment by panelists and produces kefir with a smooth texture. In the study of Wulansari et al (2022) with the addition of wheat milk and starter L. casei AP, the structure of goat milk kefir increased. In this study, it was proven that the addition of wheat milk caused the addition of total solids to goat milk kefir.…”
Section: Kefirmentioning
confidence: 99%
See 1 more Smart Citation
“…The oat milk and Lactobacillus casei AP were also added to goat milk to investigate their effects on the quality of goat milk kefir. 113 The results showed that the combined addition of oat milk and Lactobacillus casei AP increased the viscosity of goat milk kefir, leading to the loss of the unnecessary dehydration process. In addition, oat milk was used to develop many new oat beverages, such as oat milk coffee (Oatly and Starbucks) and oat milk tea.…”
Section: Food and Function Reviewmentioning
confidence: 99%
“…Then, the mixture was homogenized for 2 min in a blender (LG brand) to mash all the whole particles. The composition of the oat milk was 1.78% fat, 12.4% solid nonfat (SNF), 0% lactose, 1.56% protein, 85.8% water, 11,399 mPa viscosity, and pH 6.6 (Wulansari et al, 2022b).…”
Section: Preparation Of Oat Milkmentioning
confidence: 99%